The Divergent Effects of CDPPB and Cannabidiol on Fear Extinction and Anxiety in a Predator Scent Stress Model of PTSD in Rats - Shallcross, John; Hámor, Peter; Bechard, Allison R.; Romano, Madison; Knackstedt, Lori; Schwendt, Marek (Frontiers in Behavioral Neuroscience, 2019)
Post-traumatic stress disorder (PTSD) is a disorder with no clear FDA-approved treatments that reduce symptoms in the majority of patients. PTSD individuals possess an impaired capacity for extinguishing fear memory associations. As such, considerable focus has been given to the development of extinction-enhancing pharmacological agents to be used in combination with PTSD treatments. Here we use a predator-threat animal model of PTSD to test the ability of two compounds to enhance contextual fear extinction and reduce anxiety. Mirroring the heterogeneity observed in human response to trauma, an exposure to predator threat, including the fox odor TMT, have been shown to induce long-term changes in anxiety behavior in only subsets of “susceptible” rats. Here, two weeks following a ten-minute exposure to a predator odor, rats were classified into stress-Susceptible (Sus) and stress-Resilient (Res) phenotypes using cut-off behavioral criteria for elevated plus maze and acoustic startle response performance. One week following classification, Sus rats underwent three days of context fear extinction. We found that Sus rats increased freezing from day one to day two. Treatment with the mGlu5 positive allosteric modulator CDPPB, but not the phytocannabinoid cannabidiol (CBD), prior to sessions resulted in reduced freezing. CDPPB administration resulted in an increase of Fos immunoreactive cells in the medial prefrontal cortex, indicative of increased neuronal activity. Finally, we used the light-dark box test to measure phenotypic differences and the effects of CDPPB and CBD on unconditioned anxiety two weeks after classification. We found that Res rats showed less anxiety compared to Sus rats, and that CBD, but not CDPPB, administered prior to testing was anxiolytic in Sus rats. Taken together, the present data indicate that mGlu5 PAMs such as CDPPB hold promise for treating human PTSD patients as they enhance extinction of fear without increasing general anxiety. Polytherapy with medications such as CBD may be necessary in order to attenuate general anxiety and future directions will explore this hypothesis.